Odpowiedzi

2009-11-12T22:26:21+01:00
A) x+2y=3
2x+3y=7

x=3-2y
2(3-2y)+3y=7

x=3-2y
6-4y+3y=7

x=3-2y
-4y+3y=7-6

x=3-2y
-y=1/-1

x=3-2y
y=-1

y=-1
x=3-2*(-1)

y=-1
x=3+2

y=-1
x=5

b) 3x+y=5
2x+4y=8

y=5-3x
2x+4(5-3x)=8

y=5-3x
2x+20-12x=8

y=5-3x
-10x=8-20

y=5-3x
-10x=-12/-10

y=5-3x
x=1,2

x=1,2
y=5-3*(1,2)

x=1,2
y=2,4

c) jest zły przykład bo są 3 y a nie ma x
d) x+y=1
x-2y=2

x=1-y
(1-y)-2y=2

x=1-y
1-y-2y=2

x=1-y
-3y=2-1

x=1-y
-3y=1/-3

x=1-y
y=-0,3

y=-0,3
x=1-(-0,3)

y=-0,3
x=1,3
licze na naj.